John F. Kennedy : The Life, The Presidency, The Assassination - Shircore, Ian and Southwell, David (London Andre Deutsch, 2013)
"John F. Kennedy: the life, the presidency, the assassination examines every key event of J.F.K.'s tenure as President, as well as his hotly debated acts of heroism during World War II, his groundbreaking work in Congress and the Senate and the controversial 1960 election that heralded his supremacy. The book also reveals Kennedy's fascinating private life -- from the turbulent relations within the Kennedy family, to his tainted marriage to Jacqueline Bouvier -- before closing with the an assessment of Kennedy's legacy"--Publisher's description.
Include Illustration
Keywords: Presidents -- United States -- Politics and government